Active dendritic cell immunotherapy for glioblastoma: Current status and challenges. (April 2015) - Polyzoidis, Stavros; Tuazon, Juel; Brazil, Lucy; Beaney, Ronald; Al-Sarraj, Safa Taha; Doey, Lawrence; Logan, Jamie; Hurwitz, Victoria; Jarosz, Jozef; Bhangoo, Ranjeev; Gullan, Richard; Mijovic, Aleksandar; et al.
Abstract Dendritic cell (DC) immunotherapy is developing as a promising treatment modality for patients with glioblastoma multiforme (GBM). The aim of this article is to review the data from clinical trials and prospective studies evaluating the safety and efficacy of DC vaccines for newly diagnosed (ND)- and recurrent (Rec)-GBM and for other high-grade gliomas (HGGs). By searching all major databases we identified and reviewed twenty-two (n = 22) such studies, twenty (n = 20) of which were phase I and II trials, one was a pilot study towards a phase I/II trial and one was a prospective study. GBM patients were exclusively recruited in 12/22 studies, while 10/22 studies enrolled patients with any diagnosis of a HGG. In 7/22 studies GBM was newly diagnosed. In the vast majority of studies the vaccine was injected subcutaneously or intradermally and consisted of mature DCs pulsed with tumour lysate or peptides. Median overall survival ranged between 16.0 and 38.4 months for ND-GBM and between 9.6 and 35.9 months for Rec-GBM. Vaccine-related side effects were in general mild (grade I and II), with serious adverse events (grade III, IV and V) reported only rarely. DC immunotherapy therefore appears to have the potential to increase the overall survival in patients with HGG, with an acceptable side effect profile. The findings will require confirmation by the ongoing and future phase III trials.